2016
DOI: 10.9790/0853-1509142631
|View full text |Cite
|
Sign up to set email alerts
|

“A study of Serum levels of LDH and ALP in carcinoma breast: An Observational study”

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous study found that malignant lesions of breast cancer were more common in rural areas as compared to urban. (15) This could be due to poor medical aid in rural areas, lower socioeconomic status, and illiteracy. (16) These studies not agree with the present study, this disagreement may be related to a non-homogenous samples.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found that malignant lesions of breast cancer were more common in rural areas as compared to urban. (15) This could be due to poor medical aid in rural areas, lower socioeconomic status, and illiteracy. (16) These studies not agree with the present study, this disagreement may be related to a non-homogenous samples.…”
Section: Discussionmentioning
confidence: 99%